Right Laparoscopic Adrenalectomy in a Bitch - de Souza, Fernando Wiecheteck; Gomes, Cristiano; Kasper, Priscila Natasha; de Oliveira, Marília Teresa; ScusselFeranti, João Pedro; TrichesDornbusch, Peterson; Huppes, Rafael Ricardo; Daniel, Lucas Lubasinski; Brun, Maurício Veloso; Sprada, Arícia Gomes; et al. (Acta Scientiae Veterinariae, 2016)
Background: The medical procedure of Laparoscopic adrenalectomy is common in human medicine; however, this is not true in veterinary medicine, where it isperformed rarely. The current treatment of choice for adrenal neoplasms is total adrenalectomy, unless there is a pre-operativediagnosis of metastasis that precludes surgery. The laparoscopic approach option becomes an interesting alternative because, through this technique,it has shown good results. In this report, we demonstrate the experience of a case in which we performed unilateral laparoscopic right adrenalectomy, without caudalvena cava invasion, in a dogsuffering from hyperadrenocorticism caused by adrenocortical carcinoma. Case: A 9-year-old beagle bitch, 12 kg in weight, showedpolyphagia, polydipsia, polyuria, pendular abdomen, thin and dark skin, lumbar alopecic areas and lethargy. The team carried out Complete Blood Count (CBC), blood chemistry (liver and renal functions) and urine sampling by cystocentesis for urinalysis and bacterial culture. All exams had normal results, except for ALP, which reached levels higher than 150 UIL-1. On abdominal radiographic examination, we noted mild adrenal enlargement, and by ultrasonography, it was possible to identify adrenal asymmetry and right adrenal enlargement (2.8x2x2.15 cm) in relation to the left gland (2x1x1.5 cm). As a treatment for adrenal neoplasm-dependent HAC, we recommended the execution of total right adrenalectomy execution. The videosurgery used four accesses arranged in the right hypogastric region; the diameters were 10 (two), 5, and 3mm. The adrenal gland was carefully dissected with the aid of laparoscopic forceps; during the intraoperative period, there was a small laceration of the abdominal phrenic vein that resulted in bleeding, which was overcome with two titanium clips. The dog had an excellent recovery, and the team discharged it 48 h after the procedure. The signs of hyperadrenocorticism disappeared about two weeks after surgery. One year after having the procedure, the animal remainswell and has no signs of tumor recurrence or Cushing’s syndrome. Discussion: The choice laparoscopic approach provided less invasiveness in surgical access, reduced animal convalescence, and provided image magnifcation for the more accurate dissection of the adrenal gland. Some reports that middle-aged to older bitches were the most predisposed to present adrenal neoplasm-dependent HAC, and generally, in unilateral form, characteristics which are presented in this report. Among the clinical signs and observed in this report, are polydipsia, polyphagia, tachypnea, alopecia, and skin hyperpigmentation. That recommended the low-dose dexamethasone suppression test to diagnose Cushing’s syndrome and the endogenous ACTH test to distinguish hypophysary from adrenocorticotrophic HAC. The same tests were performed in the case reported here, as these are also important to establish the fnal diagnosi sand refer the total adrenalectomy realization. In the current case report, access to the right hypogastric region using four videosurgery portals provided good surgical access. Towards the hospital convalescence time, the animal was discharged early, just 48 h post-operatively; remission of HAC clinical signs occurredwithin three weeks, and the survival already reached 12 months.To the best of the authors’ knowledge, this is the frst successful case of total right adrenalectomy without caudal vena cava invasion via the laparoscopic route as treatment for adrenocortical carcinoma in the national literature. Keywords: adrenal gland, neoplasm, videosurgery, dogs.